2022
DOI: 10.7759/cureus.32268
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rheumatic Diseases on Oral Health-Related Quality of Life

Abstract: Introduction Oral-health-related quality of life (OHRQoL) represents a part of the general health-related quality of life (HRQoL). This OHRQoL indicates someone's subjective knowledge of a patient's oral health status, which is mostly associated with physical conditions and general HRQoL issues. A report by the World Health Organization labeled rheumatic and musculoskeletal diseases as the second most reported cause of disability worldwide. Considering their potential influence on the masticatory sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…However, Nawata et al indicated that the uncontrolled nature of severe RA itself, rather than the side effects of medications, directly lead to mouth ulcers ( Nawata et al, 2021 ). Additionally, RA can contribute to oral dryness, thereby compromising the mouth’s protective mucosal layer, which increases susceptibility to trauma and infection, potentially resulting in mouth ulcers ( Aloyouny et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Nawata et al indicated that the uncontrolled nature of severe RA itself, rather than the side effects of medications, directly lead to mouth ulcers ( Nawata et al, 2021 ). Additionally, RA can contribute to oral dryness, thereby compromising the mouth’s protective mucosal layer, which increases susceptibility to trauma and infection, potentially resulting in mouth ulcers ( Aloyouny et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%